Perancangan Prediksi Produksi Teh Menggunakan Metode Fuzzy Tsukamoto Berbasis Web - Rozali Ilham; Harfebi Fryonanda (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
Nowadays, technology is also widely applied in various fields with various needs. Innovations will continue to be developed to create even more efficient technologies for various fields. Based on data from. Various sectors, such as education, business, tourism, to the agricultural sector, widely use websites. There are various implementations or applications of technological developments in agriculture, one of which is the application of calculating an agricultural product—tea production in Kaligua in 2018 experienced ups and downs due to less stable weather conditions. Calculations in determining an agricultural product can use several calculation methods, one of which is the Tsukamoto fuzzy method. Tsukamoto's fuzzy method is an extension of monotone reasoning. In Tsukamoto's method, every consequence has a rule in the form of IF-THEN that must be represented in a fuzzy set with a monotone arrangement function. So this requires a system that can produce predictions in tea production in Kaligua tea plantations to meet market needs. The solution offered is a production prediction system in Kaligua plantations using the Tsukamoto fuzzy method. The prediction results obtained in this study were a 36% increase in tea sales production.